Association between electronic media use, development milestones and language in infants - Stamati, Maian (2022)
The use of electronic media has increased in early childhood. During early childhood, language and motor skills are important for the development of other cognitive skills. Therefore, it becomes essential to study how the use of screens is associated with these important skills in the first years of life. The objective of the following research was to describe the use of electronic media (i. e., TV, cellphone and tablet) and its association with language and developmental milestones in the first years of life. Participants were 253 primary caregivers of infants between 2 to 48 months (M = 30.17 months, SD = 10.82, female = 124). Parental reports of infant media use, motor and language development milestones, the MacArthur-Bates Communicative Development Inventory (CDI) and the Permanent Household Survey (EPH) for sociodemographic variables were used. The results showed that, on average, infants began to use screens during the first year of life at an average of one hour per day with TV as the most used medium and video viewing as the activity they did the most. The number of hours of devices usage was positively associated with lexical density and sentence use. Furthermore, starting device use at a later age was associated with lower scores in language reports and later milestones of motor and language development. No differences were found based on the type of device content and sociodemographic variables. Results indicate that the excessive use of screens could affect some early skills, although it is necessary to investigate the context in which they are used.